Safety and effectiveness of a non-electric infant warmer for hypothermia in Rwanda: A cluster-randomized stepped-wedge trial. (April 2021) - Uwamariya, Josee; Mazimpaka, Christian; May, Leana; Nshimyiryo, Alphonse; Feldman, Henry A.; Sayinzoga, Felix; Umutesi, Sharon; Gadgil, Ashok; Rapp, Vi H.; Nahimana, Evrard; Hansen, Anne
Abstract: Background: Neonatal hypothermia is a common source of morbidity and mortality in low resource settings. We developed the Dream Warmer, a low cost, re-usable non-electric infant warmer to prevent and treat hypothermia. Methods: We conducted a cluster-randomized stepped-wedge trial. The primary aim was to assess the effect on overall euthermia rates of introducing the warmer compared to standard of care in rural Rwandan hospitals. The secondary aims were to assess effects of warmer introduction on mortality, as well as the safety and feasibility of the warmer. Ten district hospitals participated in the study from November 19th 2019 to July 15th 2020. Patients were eligible to use the warmer if they were 1) hypothermic (temp < 36·5 °C) or 2) or at risk of hypothermia (weight < 2·5 kg or estimated post menstrual age < 35 weeks) when Kangaroo Mother Care was not available. An encounter was defined as the data from an individual infant on a single day. Trial of a Non Electric Infant Warmer for Prevention and Treatment of Hypothermia in Rwanda [NCT03890211]. Findings: Over the study period, 3179 patients were enrolled across the ten neonatal wards, yielding 12, 748 encounters; 464 unique infants used the warmer 892 times, 79% eligible due to hypothermia. Because of limited study nurse resources, the warmer was used in only 18% of eligible encounters. Despite this low rate of warmer use, the rate of euthermia rose from 51% (95% CI 50−52%) of encounters pre-intervention to 67% (66−68%) post-intervention; p  < 0·0001. Among the encounters in which the warmer was used, only 11% (9–13%) remained hypothermic. While mortality rates pre- and post-intervention did not change, mortality rate among those who used the warmer was significantly lower than among those who did not (0·9% vs 2·8%, p  = 0·01). Use of the warmer did not affect hyperthermia rates. There were no safety concerns or instances of incorrect warmer use. Interpretation: Introduction of the warmer increased rates of euthermia with no associated safety concerns.